Phytonutrients and their neuroprotective role in brain disorders - Adhikary, Krishnendu; Ganguly, Krishnendu; Sarkar, Riya; Abubakar, Md.; Banerjee, Pradipta; Karak, Prithviraj (Frontiers in Molecular Biosciences, 2025)
In the twenty-first century, cognitive impairment is a significant health problem. Function is substantially impaired by a number of neuropsychiatric and neurodegenerative diseases, such as Parkinsonism, schizophrenia, major depressive disorder, Alzheimer’s disease and other types of cognitive impairment, cerebrovascular disabilities, seizure-related disorders, and brain traumas. Over time, a number of chemical messengers and signaling molecules have been identified as potential targets for treatment, and tests have been performed against these targets using both conventional and novel chemicals. Phytochemicals derived from medicinal plants are essential for preserving the chemical balance of the central nervous system because they change the activity of major inhibitory receptors that receive neurotransmitters. Many herbs have been used in conventional medicine to treat cognitive problems. Although the presence of receptors that are responsible or transporters for compounds called polyphenols and other phytochemicals in brain regions remains to be determined, multiple target substances seem to be a promising class of treatment options for treating disorders with multifactorial origins. Additional studies suggest that flavonoids possess significant anti-inflammatory properties in the brain, making them a promising therapeutic option for conditions such as ischemic or hemorrhagic stroke, as well as chronic neuroinflammatory disorders like Parkinson’s and Alzheimer’s disease. This review highlights how phytochemicals contribute to the protection against brain disorders and explores the underlying mechanisms involved in their action. It also emphasizes the core biological processes, providing deeper insight into the therapeutic potential of phytochemicals in the treatment of neurological conditions.